Importance of Basic Psychological Needs Satisfaction in Higher Education: A Systematic Literature Review - Bijak Aditia Hutomo; Farida Kurniawati (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
This systematic literature review analyzes previous studies on basic psychological needs satisfaction in higher education. Five international databases were used in this study, including EBSCOHost, Science Direct, Scopus, Springer, and Taylor & Francis, to gather publications from 2019 to 2023 with a quantitative approach, whether cross-sectional, longitudinal, or experimental. Out of the initial 561 articles, 27 passed the screening process, which used the population, intervention, comparison, and outcome (PICO) model to create inclusion criteria. The writing guideline of this research follows The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Results of the study showed a positive relationship between basic psychological needs satisfaction and motivation, well-being, student engagement, and academic achievement. The importance of basic psychological needs satisfaction in higher education can initiate collaboration among institutions, lecturers, and college students, leading to improved motivation, well-being, engagement, and academic outcomes. Keywords: self-determination theory, basic psychological needs, higher education, motivation, academic achievement